2016
DOI: 10.1038/srep35452
|View full text |Cite
|
Sign up to set email alerts
|

Tissue, developmental, and caste-specific expression of odorant binding proteins in a eusocial insect, the red imported fire ant, Solenopsis invicta

Abstract: Insects interact with the surrounding environment via chemoreception, and in social insects such as ants, chemoreception functions to mediate diverse behaviors including food acquisition, self/non-self recognition, and intraspecific communication. The invasive red imported fire ant, Solenopsis invicta, has spread worldwide, displaying a remarkable environmental adaptability. Odorant binding proteins (OBPs) are chemical compound carriers, involved in diverse physiological processes including odor detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…). For previously known OBPs, the topology of our phylogenetic tree agrees with previously published trees (Gotzek et al ; Zhang et al ), with the exception of the position of SiOBP15 (low bootstrap values in all trees) and SiOBP5 .…”
Section: Resultssupporting
confidence: 89%
“…). For previously known OBPs, the topology of our phylogenetic tree agrees with previously published trees (Gotzek et al ; Zhang et al ), with the exception of the position of SiOBP15 (low bootstrap values in all trees) and SiOBP5 .…”
Section: Resultssupporting
confidence: 89%
“…There is evidence supporting the similarity of worker and male OBP expression down to low levels. A study of fire ant antennal OBP mRNA ( Zhang et al 2016 ) shows a similar pattern to our proteomics data in Table 1 for high-level transcripts, but no gap between workers and males appears in the low-level OBP transcripts, which are at about the same levels.…”
Section: Discussionsupporting
confidence: 81%
“…Genes may also neofunctionalize in terms of gene expression. Prior studies have shown that many OBPs, including Gp‐9 and SiOBP12 , are expressed in nonantennal tissues (Morandin et al, ; Pracana et al, ; Zhang, Wanchoo, Ortiz‐Urquiza, Xia, & Keyhani, ). We tested whether SiOBP12 (in an assay that cannot distinguish between paralogs) was also differentially expressed in the worker heads (without antennae), thoraces, and abdomens using qRT‐PCR assays.…”
Section: Resultsmentioning
confidence: 99%